Analisis Manajemen Keselamatan Kerja pada Pengoperasian Alat Tangkap Purse Seine di KM. Pelita Perkasa PT. Manunggal Suko Jaya, Sorong, Papua Barat Daya - Rahmatang Rahmatang; Mahdir Ramadhan; Arham Rumpa; Angraeni Angraeni (Syntax Corporation Indonesia, 2024)
The purpose of this study is to identify and describe the operation of Purse Seine fishing gear on KM. Pelita Perkasa. The data collection used in KPA activities is observation, interview, and library research. The data that will be obtained using this method are in the form of primary data and secondary data. The data analysis method that will be used in the Final Practice Work (KPA) is descriptive analysis (quantitative and qualitative). Results, Operation of purse seine fishing gear on KM. Pelita Perkasa is carried out with procedures and procedures that are in accordance with work safety standards. The organizational structure and construction of the ship have also met the safety requirements. There are several work activities on board the KM purse seine. Pelita Perkasa which has the potential to cause work accidents, such as the use of a winch, lifting the net, and activities on a slippery deck. Work accidents that often occur in KM crew. Pelita Perkasa was injured, fractured, and plunged into the sea, among others.